Analisis Bahasa “Nasehat Penuntut Ilmu Imam al-Syafi’i” Melalui Picture Theory Ludwig Wittgenstein - Anwar, Khairil; Helmi Syaifuddin (An Naba, 2024)
This research aims to look at Wittgenstein's Picture Theory concept in his work Tractatus Logico-Philosophicus and to analyze the language of Imam al Syafi'i's advice to science students. This research is qualitative research with the type of library study. The data source in this research is taken from the book Tractatus Logico-Philosophicus as well as books and articles related to the advice of Imam al Syafi'i and Wittgenstein's thoughts. This research data was validated by adopting Miles and Hubermen's qualitative validation steps. The results of this research show that: 1) Wittgenstein's thinking in his book was the result of the development of his two mentors, namely Gottlob Frege and Bertrand Russell. Picture Theory emerged because of Wittgenstein's disagreement with the language of philosophers in explaining his concepts. 2) The results of the analysis of the language of Imam al-Syafi'i's scientific advice are that there are meaningful and meaningless propositions in the advice. This is based on the fact that picture theory only accepts propositions that can be explained in reality and does not pay attention to propositions that cannot be described empirically.